2009
DOI: 10.1091/mbc.e09-02-0109
|View full text |Cite
|
Sign up to set email alerts
|

Udu Deficiency Activates DNA Damage Checkpoint

Abstract: Udu has been shown to play an essential role during blood cell development; however, its roles in other cellular processes remain largely unexplored. In addition, ugly duckling (udu) mutants exhibited somite and myotome boundary defects. Our fluorescence-activated cell sorting analysis also showed that the loss of udu function resulted in defective cell cycle progression and comet assay indicated the presence of increased DNA damage in udu tu24 mutants. We further showed that the extensive p53-dependent apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 67 publications
7
41
0
Order By: Relevance
“…Further, analysis of mice engineered to lack YY1 in B cell progenitors has demonstrated that YY1 has a role in immunoglobulin gene rearrangement (36), a process that requires DNA repair. With regard to Gon4l, studies of zebrafish bearing null mutations in the Gon4l ortholog ugly duckling have provided evidence that this protein is important for cell division and genome stability in addition to the regulation of gene expression (11,12). These findings, combined with our observations linking Gon4l to Sin3a and YY1, suggest that Gon4l may be important for pathways in addition to those that mediate gene repression.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Further, analysis of mice engineered to lack YY1 in B cell progenitors has demonstrated that YY1 has a role in immunoglobulin gene rearrangement (36), a process that requires DNA repair. With regard to Gon4l, studies of zebrafish bearing null mutations in the Gon4l ortholog ugly duckling have provided evidence that this protein is important for cell division and genome stability in addition to the regulation of gene expression (11,12). These findings, combined with our observations linking Gon4l to Sin3a and YY1, suggest that Gon4l may be important for pathways in addition to those that mediate gene repression.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, it is likely that other cofactors for Gon4l remain to be identified. Of note in this regard, a recent report provided evidence that the PAH repeats and SANT domain of zebrafish Gon4l mediate interaction with the proteins MCM3 and MCM4 (12), which are important for DNA replication but likely function in additional pathways (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GON4L also regulates gene expression in developmental pathways of C. elegans, D. melanogaster , and D. rerio (zebrafish). Absence of GON4L causes cell cycle arrest and increased cellular apoptosis in developing zebrafish embryos (4345). Despite these roles, no evidence of its association with human cancer growth or its mechanism of action in this setting had been shown until our work.…”
Section: Discussionmentioning
confidence: 99%
“…SANT and homeodomains function in the regulation of transcription (Boyer et al, 2004;Hueber and Lohmann, 2008). Interestingly, BLAST searches revealed that the PAH repeats of Mute-L are 28% identical to that of zebrafish Ugly duckling (Udu), a nuclear protein required for somite development (Lim et al, 2009;Liu et al, 2007) and 27% identical to that of human GON4L or YARP (YY1AP-related protein 1), a nuclear protein with suggested transcriptionalregulator-like functions (supplementary material Fig. S1).…”
Section: Identification and Molecular Cloning Of Mutementioning
confidence: 99%